Fatal Pneumonia Associated With a Novel Genotype of Human Coronavirus OC43 - Lau, Susanna Kar Pui; Li, Kenneth Sze Ming; Li, Xin; Tsang, Ka-Yan; Sridhar, Siddharth; Woo, Patrick Chiu Yat (Frontiers in Microbiology, 2022)
Since its first discovery in 1967, human coronavirus OC43 (HCoV-OC43) has been reported to be associated with mild self-limiting upper respiratory infections worldwide. Fatal primary pneumonia due to HCoV-OC43 is extremely rarely. In this study, we describe a case of fatal primary pneumonia associated with HCoV-OC43 in a 75-year-old patient with good past health. The viral loads of the respiratory tract specimens (bronchoalveolar lavage and endotracheal aspirate) from diagnosis to death were persistently high (3.49 × 106 to 1.10 × 1010 copies/ml). HCoV-OC43 at a level of 6.46 × 103 copies/ml was also detected from his pleural fluid two days before his death. Complete genome sequencing and phylogenetic analysis showed that the present HCoV-OC43 strain forms a distinct cluster with three other HCoV-OC43 strains from the USA, with a bootstrap value of 100% and sharing 99.9% nucleotide identities. Pairwise genetic distance between this cluster and other HCoV-OC43 genotypes ranged from 0.27 ± 0.02% to 1.25 ± 0.01%, whereas the lowest pairwise genetic distance between existing HCoV-OC43 genotypes was 0.26 ± 0.02%, suggesting that this cluster constitute a novel HCoV-OC43 genotype, which we named genotype I. Unlike genotypes D, E, F, G and H, no obvious recombination event was observed for this novel genotype. Structural modeling revealed that the loop with the S1/S2 cleavage site was four amino acids longer than other HCoV-OC43 strains, making it more exposed and accessible to protease, which may have resulted in its possible hypervirulence. Antiviral agents for CoV infections in human are of urgent need.